TPO-Ab plays a role in arterial remodeling in patients with intracranial stenosis. (January 2019) - Zhang, Xuting; Zhou, Ying; Ding, Wenhong; Zhang, Ruiting; Yan, Shenqiang; Deng, Yujie; Gao, Feng; Lou, Min
Abstract: Background and aims: Intracranial stenosis (ICS), the common cause of ischemic stroke worldwide, is associated with a high risk of recurrent stroke. We aimed to investigate the relationship between arterial remodeling and antithyroid peroxidase-antibody (TPO-Ab) level in ICS and the effect of TPO-Ab level on the migration of vascular smooth muscle cells (VSMCs). Methods: We analyzed data of mild-to-severe ICS patients with normal thyroid function who underwent high-resolution magnetic resonance imaging in our center. Vessel area (VA), lumen area, wall area and plaque size were assessed at the most narrowed lumen (MNL) and reference site, respectively. The remodeling index (RI) was defined as VAMNL/VAreference. Negative remodeling (NR) or non-NR was defined as RI ≤ 0.95 or > 0.95. A scratch-wound healing assay was also designed to analyze the impact of TPO-Ab level on migration of VSMCs, which were isolated from thoracic aorta segments of Sprague Dawley rats. Results: A total of 88 patients were included. Patients with elevated TPO-Ab had smaller VA, wall area, plaque size and RI than those with normal level ( p < 0.05). Elevated TPO-Ab was significantly associated with NR after adjusting for demographic and vascular risks (odds ratio 10.629, 95% confidence interval, 1.842–61.327, p = 0.008). The rate of VSMCs migration was significantly increased after culture with TPO-Ab (TPO-Ab 1 μg/ml vs . Mock, 29.8% vs . 12.0%, p < 0.01). Conclusions: Elevated TPO-Ab in ICS patients was related to NR. TPO-Ab could promote VSMCs migration, which might be involved in the NR of intracranial artery. Graphical abstract: Highlights: Intracranial stenosis (ICS) had negative remodeling (NR) and positive remodeling pattern. Elevated thyroid peroxidase antibody (TPO-Ab) was correlated with NR. TPO-Ab increases vascular smooth muscle cells (VSMCs) migration. VSMCs migration may be involved in the process of NR.